Sensitivity Assay of Resistant Escherichia coli to Fosfomycin, Kanamycin, Rifampicin, Ceftriaxone, Imipenem, and Vancomycin - Tina Rostinawati Rostinawati; Rikadianan rikadianan; Imam Adi Wicaksono (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Antibiotic resistance is a major global health problem and continues to increase, so there is a need forbetter evaluation and therapeutic advice for Urinary Tract Infection (UTI) patients. It had isolated E. colifrom clinical isolates that were resistant to antibiotics of β-lactam, the first generation of cephalosporinand fluoroquinolone. Characterization of bacterial sensitivity should be analyzed to other antibioticswith different mechanisms. Therefore, this study aims to analyze the antibiotic activity of fosfomycin,kanamycin, rifampicin, ceftriaxone, imipenem, and vancomycin against to resistant Escherichia coliclinical isolates of UTI. The sensitivity test in this study used the Kirby-Bauer disc diffusion methodand data analysis using SPSS version 24. The results revealed the diameter of inhibition zone (mm) ofantibiotics of fosfomycin, ceftriaxone, imipenem, kanamycin, rifampicin, and vancomycin respectivelyi.e. 38±1; 36.3±1.15; 35±1; 31.6±1,15; 28±1; and 26.3±0.17. Based on statistical analysis there weresignificant differences in the activity of fosfomycin, ceftriaxone, imipenem, kanamycin, rifampicin,and vancomycin.